Variable forgetting factor RLS algorithm based on dynamic equation of gradient of mean square error - So, C F; Leung, S H (Electronics letters, 2001)
A new variable forgetting factor RLS adaptive algorithm, is introduced. The control of the forgetting factor is based on the dynamic equation of the gradient of the mean square error. Compared with other algorithms, the new algorithm gives fast tracking, has a small mean square model error, and is insensitive to SNR.